Efficient approach to iron/nitrogen co-doped graphene materials as efficient electrochemical catalysts for the oxygen reduction reaction - Dong, Qingqing; Zhuang, Xiaodong; Li, Zhi; Li, Bin; Fang, Bin; Yang, Cunzhong; Xie, Haifen; Zhang, Fan; Feng, Xinliang (Journal of Materials Chemistry A, 2015)
Cyclopentadienyliron (CpFe) groups have been successfully attached on the surface of reduced graphene oxide (rG) by a ligand-exchange reaction of ferrocene (Cp2Fe) and rG to produce CpFe-modified reduced graphene oxide (rGFeCp), which exhibits good processability in many organic solvents. In a similar one-pot reaction, graphite was efficiently exfoliated using Cp2Fe as the intercalator to form CpFe-attached free-standing graphene nanosheets (GFeCp, ∼10 layers). Upon pyrolysis and ammonia activation, rGFeCp and GFeCp were converted to iron/nitrogen co-doped porous graphenes, namely, rGFe-800a and GFe-800a, respectively. The obtained rGFe-800a exhibited good electrochemical performance for the oxygen reduction reaction (ORR) under alkaline conditions (0.1 M KOH) with a low half-wave potential at -0.29 V, a dominant four-electron transfer mechanism (n = 3.5 at -1.0 V), and a maximum diffusion-limiting current density of 4.86 mA cm-2. In addition, rGFe-800a showed excellent methanol tolerance, superior to that of commercial 20% Pt/C. The effect of iron/nitrogen co-doping plays a key role in the good ORR activities of the as-prepared materials.
CRIS-Team Scopus Importer:2023-03-20